Radiometric Imaging for Monitoring and Surveillance Issues - Francesco Soldovieri; Antonio Natale; Vladimir Gorishnyak; Andrey Pavluchenko; Alexander Denisov; Lijia Chen (International Journal of Antennas and Propagation)
This paper deals with the recent advances performed by State Research Center “Iceberg” (SRC) in the field of the passive imaging at millimeter wavelengths. In particular, first the paper describes the design and the realization of two systems working in 3 mm and 8 mm wave bands, respectively. Second, the measurements collected by the two systems are enhanced by means of simple data processing strategies developed by the Institute for Electromagnetic Sensing of the Environment (IREA-CNR).